The effect of work environment and motivation on job satisfaction levels among generation Z in Bandar Lampung - Carolin Sintia Wibowo; Berlintina Permatasari (Universitas Nusa Cendana, 2026)
This study investigates the influence of work environment and work motivation on the job satisfaction of Generation Z employees in Bandar Lampung, both individually and collectively. Employing a quantitative research design, data were collected through structured questionnaires administered to 240 respondents and subsequently analysed using statistical techniques. The findings reveal that both the work environment and work motivation exert positive and significant effects on employee job satisfaction. A supportive work environment, characterised by favourable interpersonal relationships, comfortable working conditions, and organisational support, was found to enhance employees’ sense of satisfaction and well-being. Similarly, work motivation contributed significantly to increasing employee enthusiasm, engagement, and positive attitudes toward work. The combined influence of these factors demonstrates their strategic importance in improving job satisfaction among Generation Z employees, a workforce cohort known for its distinct expectations regarding workplace culture, flexibility, and career fulfilment. These findings highlight the need for organisations to develop supportive workplace environments and effective motivational practices in order to strengthen employee satisfaction and retention. Nevertheless, the study is limited to respondents located in Bandar Lampung, which may restrict the broader generalisability of the findings. Future research is therefore recommended to expand the geographical scope and incorporate additional variables, such as organisational commitment, leadership style, or employee engagement, as mediating or moderating factors to provide a more comprehensive understanding of Generation Z workplace dynamics. Keywords: Work Environment; Work Motivation; Work Satisfaction